WHEN GREEN MARKETING LICENSES NON-GREEN LUXURY CONSUMPTION: A MORAL LICENSING PERSPECTIVE - Fathayani Salsabila; Yolanda Masnita; Husna Leila Yusran (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
Introduction: Although green marketing has been widely recognized for promoting environmentally friendly products, little is known about its ability to encourage consumers to purchase non-green luxury products. Drawing on Moral Licensing Theory, this study examines how green marketing influences purchase intention through brand ethical image while considering the role of luxury brand perception. Method: A quantitative cross-sectional survey was conducted among 130 Indonesian consumers familiar with luxury brands. Data were analyzed using Structural Equation Modeling (SEM) with AMOS to test the proposed relationships. Results: Green marketing positively influenced both brand ethical image and purchase intention. Brand ethical image also significantly enhanced purchase intention, while luxury brand perception remained a significant predictor of consumers' intention to purchase non-green luxury products. These findings indicate that consumers simultaneously consider ethical evaluations and symbolic brand value in luxury purchasing decisions. Discussion: This study extends Moral Licensing Theory by demonstrating that organizational sustainability communication can generate ethical evaluations that justify consumers' intention to purchase non-green luxury products. The findings highlight that sustainability communication and luxury symbolism complement one another, providing both theoretical insights into sustainable luxury consumption and managerial guidance for integrating environmental responsibility into luxury brand strategies.